Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Prerequisites - p.4 - Factoring Polynomials - Exercises - Page 39: 58



Work Step by Step

Expression : $-9x^{2}+6x-1 = -(9x^{2}-6x+1)$ By the well known formula $(a-b)^{2} = a^{2} -2ab +b^{2}$ $(9x^{2}-6x+1) = (3x)^{2}-2(3x)(1)+1^{2} = (3x-1)^{2}$ Hence, $-9x^{2}+6x-1 = -(9x^{2}-6x+1) = -(3x-1)^{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.